A Cautionary Tale for Psychology and Higher Education in Asia: Following Western Practices of Incentivising Scholarship May Have Negative Outcomes. (March 2020) - Svare, Bruce B.
Cases of scientific fraud and research misconduct in general have escalated in Western higher education over the last 20 years. These practices include forgery, distortion of facts and plagiarism, the outright faking of research results and thriving black markets for positive peer reviews and ghost-written papers. More recently, the same abuses have found their way into Asian higher education with some high profile and widely covered cases in India, South Korea, China and Japan. Reports of misconduct are now reaching alarming proportions in Asia, and the negative consequences for individuals, institutions, governments and society at large are incalculable. The incentives for academic scientists in Asia are approaching and even surpassing those ordinarily seen in the West. Cash payments for publishing articles in high impact journals can double or even triple yearly salaries in some cases. Combining this environment with the simultaneous pressure to obtain oftentimes scarce funding for research has produced a culture of unethical behaviour worldwide. This article assesses three important issues regarding scientific fraud and research misconduct: distorted incentives for research and overreliance upon metrics, damage to the integrity of higher education and public trust and improving research environments so as to deter unethical behaviour. This is especially crucial for emerging Asian countries, in particular Association for Southeast Asian Nations (ASEAN), whose scientific infrastructure is less developed, but nonetheless has the potential to become a major player in the development of psychology as well as Science, Technology, Engineering and Mathematics (STEM) research and training.